Current status, hotspots and frontiers of ion channel-related research in glioblastoma: a bibliometric analysis from 2005 to 2024 - He, Zefeng; Liu, Jing; Jin, Qianxu; Ren, Shangkun; Liu, Liang; Liu, Yingzi (Frontiers in Oncology, 2025)
Glioma is the most common primary tumor of the central nervous system, with glioblastoma being its predominant pathological type. In recent years, research has demonstrated that ion channels are intricately linked with numerous biological processes in tumor cells, including apoptosis and migration, among others. This study employs bibliometric analysis to systematically examine and synthesize the knowledge structure and research focal points in the field of glioblastoma ion channels. Publications related to ion channels in glioblastoma, published between January 1, 2005 and December 31, 2024, were retrieved from the Web of Science Core Collection (WoSCC). The dataset comprises 764 articles and 234 reviews. Utilize VOSviewer, CiteSpace, Bibliometrix, and Excel to conduct an in-depth analysis and visualization of scholarly contributions based on country, institution, journal, and author. Additionally, examine highly cited publications, references, and keywords. From 2005 to 2024, the number of publications in this field has shown a consistent annual increase. The University of Alabama and Cancer are among the leading institutions and journals. Sontheimer Harald, from the United States, is the most prolific author in this field. The analysis of highly cited publications and co-cited references indicates that the research background and foundation focus on elucidating the mechanisms by which ion channels influence the onset and progression of glioblastoma. Keyword analysis indicated that “tumor microenvironment” (burst strength: 4. 67), “Ca2+ activated K+ channel” (burst strength: 3. 98), and “chloride channels” (burst strength: 3. 59) have been the keywords exhibiting the highest burst intensity over the past two decades. The keywords that have emerged with higher frequency in the past five years include “tumor microenvironment” (burst strength: 4. 67), “receptor” (burst strength: 3. 11), and “channels” (burst strength: 3. 11). Research on ion channels in glioblastoma has emerged as a prominent and rapidly evolving field of interest. Previous studies have primarily focused on the examination of specific ion channels and their functionalities. However, recent keyword analysis highlights the necessity to explore the interaction between ion channels and the tumor microenvironment. Meanwhile by integrating single-cell spatial transcriptomics and nanoparticle technologies, we can significantly enhance the efficacy of ion channel-targeting therapies.